Development of a multiple-unit system: Tablets containing amlodipine besylate which have different release kinetics - TEKDEMİR, OZAN; UĞURLU, TİMUÇİN (MARMARA UNIV, 2020)
Multiple-unit systems may include tablets, capsules, pellets in a single administration. Once-a-day administration of Amlodipine Besylate (AML) accounts for fluctuation of plasma drug concentrations between dosing intervals. The aim of this study is to develop an extended-release (ER) and an immediate-release (IR) tablet to overcome the fluctuation of plasma drug concentrations. To achieve this purpose, 9 IR tablets and 6 ER tablet formulations were developed. The dissolution media for IR tablets was pH 2 for 1 hour and the dissolution media for ER tablets was pH 2 for 2 hours, and afterwards was pH 6.8 for 10 hours. The amount of AML released into the dissolution media was measured by Mettler Toledo UV 5 at a wavelength of 238 nm. The dissolution data of IR and ER tablets were statically evaluated. The highest dissolution rate for IR tablets (93%) was achieved with the IR-5 formulation. For ER tablets, a 50% drug release was achieved with the ER-1 and ER-4 formulation. The drug release kinetics of all ER tablets were calculated and subsequently the ER-1 formulation, which has Higuchi drug release kinetics, was chosen as the ER tablet. Lastly, a dissolution study of the selected formulations (IR-5 and ER-1) was conducted in the same vessel. After 12 hours of the dissolution study, drug release was found to be 79% +/- 0,92 (close to 75% which was targeted). Multiple-unit systems that have different tablet formulations in one administration could be used to enhance drug release kinetics that cannot be achieved with conventional tablets.
Keywords: Multiple unit system; amlodipine besylate; immediate release tablet; extended release tablet; fluctuation of plasma drug concentration; hydroxyl propyl cellulose; sodium starch glycolate; crospovidon; ORALLY DISINTEGRATING TABLETS; DISSOLUTION ENHANCEMENT; PHARMACOKINETICS